Using Zakâh For The Establishment of Islamic Centers and Maqâṣid Al-Syarî‘ah’s Relativities - Busyro, Busyro (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2019)
One of the people who have the right to receive the zakâh mentioned in the eight aṣnâf is fî sabîlillah (people who are in a jihâd). Jihâd and all the means relating to it are the initial meaning agreed upon by most of ulama. The term fî sabîlillâh has been understood further in the context of the construction of places of worship and Islamic centers. This meaning expansion the term fî sabīlillah certainly needs to be seen in relation to maqâṣid al-syarî‘ah, especially in relation to ‘illat as one of the main instruments of maqâṣid al-syarî‘ah. The discussion by using ‘illat concluded that the development of the meaning of fî sabîlillâh to other than jihâd is permissible as long as it is intended to help individuals who struggle for the sake of the establishment of religion by financing their activities. Furthermore, this meaning is more in line with maqâṣid al-syarî‘ah.